Pentingnya penanaman nilai agama dan moral terhadap anak usia dini - Nisa Cahaya Karima; Salsabil Hasna Ashilah; Alifia Sekar Kinasih; Putri Haura Taufiq; Latipah Hasnah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2022)
The inculcation of religious and moral values towards early childhood is important to do as an early provision. One of the basic attitudes that must be had to be a good person is to have a good religious and moral attitude in behavior. The purpose of inculcation religious and moral values of children is to form the nature, good behavior from an early age because children are the next generation. The research method used is the study of literature using journals and related books. Inculcation that can be taught to children can use various learning methods such as storytelling, habituation and so forth. Violence, behavior and actions that deviate from religion and morals are still a lot going on, this is one of them due to the lack of inculcating religion and morals. With this, the inculcation of religious and moral values is important to begin from early childhood as an early structuring for good character in the future.